2018
DOI: 10.1093/beheco/ary161
|View full text |Cite
|
Sign up to set email alerts
|

Pale by comparison: competitive interactions between signaling female glow-worms

Abstract: When individuals differ in attractiveness, less attractive ones may fail to mate. In the common glow-worm, females glow to attract flying males, which prefer brighter females. We show that females move away from more attractive competitors, possibly to avoid comparison. In nature, females glowed far from each other. As distance between females may affect how males perceive female attractiveness, dim females may appear bright if close by and if comparison is not possible for males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Our finding of low mate attraction success under artificial light aligns with earlier studies that found streetlights hamper mate attraction [ 27 , 28 ]. Females can respond to light, as they move away from green LED lights imitating conspecific females [ 38 ], but bright artificial light from streetlights is stronger and of different wavelength than the glow of females, which may explain the different responses. During the day, females seldom move more than a few centimetres, as they spend the time in refuges [ 18 , 27 , 33 , 39 ], and relocation, therefore, depends on movement during the night.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding of low mate attraction success under artificial light aligns with earlier studies that found streetlights hamper mate attraction [ 27 , 28 ]. Females can respond to light, as they move away from green LED lights imitating conspecific females [ 38 ], but bright artificial light from streetlights is stronger and of different wavelength than the glow of females, which may explain the different responses. During the day, females seldom move more than a few centimetres, as they spend the time in refuges [ 18 , 27 , 33 , 39 ], and relocation, therefore, depends on movement during the night.…”
Section: Discussionmentioning
confidence: 99%
“…Here, particularly female larvae close to the pupation stage were found to disperse by moving from their more forested hunting grounds, presumably towards drier and more open habitats, where adult females were often found performing their nightly glow displays. The suitability of a given site for the displays of an adult female may be affected by at least behavioural interactions among females, population size (driving competitive interactions), visibility to ensure effective mate attraction and egg-laying opportunities nearby (Hopkins 2018;Borshagovski et al 2019;Elgert et al 2020Elgert et al , 2021Lehtonen and Kaitala 2020). Additionally, a female's egg-laying site should not be located too far from where the newly hatched offspring can find their first meal after hatching later in the season.…”
Section: Discussionmentioning
confidence: 99%
“…If the habitat types differ with regard to the distance from which females arrive to their glowing spots along the road, the observed female numbers might bias towards that specific habitat. Fourth, mate attraction success of displaying females is known to be negatively affected by the proximity of rivals (Hopkins 2018;Lehtonen and Kaitala 2020), which may also be driving females to disperse farther away from each other before or after pupation (see Borshagovski et al 2019), resulting in increased dispersal away from habitats with high larva densities (even in the absence of a specific target habitat type). More generally, our results are compatible with the idea that dispersal, even in females, can be driven by density-dependent factors, such as competition for breeding opportunities (Dobson and Jones 1985;Matthysen 2005;Arlt and Pärt 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…gadm.org), version 3.4, in April 2018 were low, and the female glowing capacity may have been challenged. After the glow measurement, we measured the width of the back shield (the pronotum) with a Vernier calliper, as it is a good proxy of female body size (Hopkins et al 2015;Borshagovski et al 2019). We measured each female only once and then returned it to its original spot of collection.…”
Section: Measurementsmentioning
confidence: 99%